Functional Recovery Among Stroke Survivors Following Targeted Nursing Interventions: Evidence from a Quasi-Experimental Study - Shruti m Roy; Peter Jasper Youtham (International Journal of Evidence Based Nursing And Practices, 2025)
Background: Stroke rehabilitation is crucial for reducing disability and improving functional independence. However, in India, nursing-led rehabilitation interventions remain underexplored. This study evaluates the effectiveness of nursing-led rehabilitation programs in improving mobility, ADL independence, and psychological well-being among stroke survivors. Methods: A quasi-experimental study was conducted at Index Medical College, Hospital & Research Center, involving 200 stroke survivors. Participants were divided into two groups: (1) Intervention Group (n = 100): Received nursing-led rehabilitation interventions along with physiotherapy. (2) Control Group (n = 100): Received routine physiotherapy only. Patients were assessed using the Functional Mobility Scale (FMS), Timed Up and Go (TUG) test, Barthel Index (BI), and PHQ-9 Depression Scale at Baseline, Week 12, and Week 24. Results: (1) Mobility Scores Improved Significantly in the Intervention Group (FMS Week 24: 4.05 ± 0.48 vs. 3.10 ± 0.52, p Conclusion: Nursing-led rehabilitation interventions significantly improve mobility, ADL independence, and psychological well-being among stroke survivors. Early integration of structured nursing-led rehabilitation into standard stroke care is recommended.
Keywords: Barthel Index; Functional Mobility; India; Nursing Interventions; PHQ-9; Stroke Rehabilitation